More sense of self-discipline, less procrastination: the mediation of autonomous motivation - Tao, Su; Jing, Yuan (Frontiers in Psychology, 2023)
Procrastination is considered a result of failed self-regulation. However, could experiencing a sense of successful self-discipline help to boost motivation and reduce procrastination? To explore this question, two studies were conducted to investigate the relationship between the sense of selfdiscipline, autonomous motivation, and procrastination. Results showed that trait sense of selfdiscipline negatively predicted general procrastination (Study 1); self-discipline primed participants procrastinated less than the control group (Study 2); autonomous motivation mediated the relationship between sense of self-discipline and procrastination (Study 1 & Study 2). These findings suggest that cultivating a sense of self-discipline can have positive effects on both autonomous motivation and procrastination, and provide useful guidance for interventions aimed at reducing procrastination.